Integrating Compliance, Risk Management, and Sustainability in Indonesian Music Festivals: Toward a Unified Governance Framework - Andang, Baharuddin (Indonesian Scientific Publication, 2025)
The governance of music festivals in Indonesia is undergoing a paradigm shift driven by rising demands for legal compliance, risk management, and sustainability. This study investigates the integration of these three dimensions within the context of Indonesian music festivals, drawing from qualitative case studies, regulatory analysis, and international best practices. The objective is to develop a scalable framework that aligns operational safety, environmental responsibility, and legal adherence. Methodologically, the research employs a qualitative design, focusing on in depth case analyses of three Indonesian festivals Java Jazz, Synchronize, and Joyland. Data were gathered through document reviews, stakeholder interviews, and thematic analysis of relevant laws and standards, including PP 56/2021, PP 109/2012, UU 27/2022, ISO 20121, and the Event Safety Guide. The results highlight effective practices in operational risk management, including the use of Safety Cells, tabletop drills, and digital monitoring tools. Sustainability efforts show traction in waste reduction, renewable energy usage, and vendor accountability, guided by ISO aligned practices. However, legal compliance remains inconsistent due to enforcement gaps and low regulatory literacy among organizers. Stakeholders such as sponsors, artists, and audiences significantly influence accountability, while public policy and interdisciplinary research emerge as enablers of broader adoption. This study concludes that an integrated governance model uniting compliance, risk, and sustainability is essential for the long term viability of Indonesian festivals. The proposed framework not only improves operational performance but also fosters public trust, stakeholder alignment, and environmental stewardship.